Die Verteilung der Primzahlen des reell-quadratischen Zahlkörpers K (√2) - Urbelis, J. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Урбялис. Распределение простых чисел вещественного квадратичного поля К (√2)J. Urbelis. Realiojo kvadratinio kūno K (√2) pirminių skaičių pasiskirstymas